Malformations of cortical development - Guerreiro,Marilisa M. (2009)
Malformations of cortical development (MCD) have been increasingly identified. The purpose of this presentation is to review the current knowledge of the MCD. Before we address this issue, we will briefly present a review of cortical development. The second part of this presentation will address the most important MCD. Finally, the last part of this presentation will address the correlation between MCD and epilepsy.